Wormlike Micelle as Drag Reducing Agent in Flow Assurance - Shian Ee, Ma (Universiti Teknologi Petronas, 2013)
Drag Reducing Agent (DRA) has been used to increase flow capacity in existing pipelines. This obviates the need to install additional booster pumps. Most of the commercial DRA is a polymeric system with high molecular weight Polyacrilamide (PAM) as typical DRA. When subjected to high shear stress, the polymeric DRA will suffer mechanical breakdown, thus reducing its effectiveness in dampening the turbulent flow inside the pipe. Consequently this reduces the drag reducing efficiency of the DRA. In this study, alternative formulation is proposed by using worm-like micelles (WLM). WLM is a visco-elastic material derived from surfactant and salt mixture. While application is widespread in consumer personal care products and flow assurance agent for district cooling and heating, utility as DRA merits further study. Since WLM has ability to break and reform under high shear stress, it can overcome the mechanical degradation common in polymeric DRA. The WLM system is formed from cationic surfactant consisting of Hexadecyltrimetyl-ammonium bromide (CTAB) at a fixed concentration of 0.15M mixed with Sodium Nitrate at 0.2 wt% to 1.0 wt%. Another system comes from Dodecyltriethylammonium Bromide (DTAB)/sodium dodecylsulfate (SDS) at the molar ratio of 27/73. The final concentration for the mixture will be in the range of 140mM to 200mM. The efficiency of WLM as potential DRA is compared with PAM DRA in a viscosity test and water flow test. Rheological behaviour of WLM is evaluated in the viscosity test as a function of apparent viscosity and shear rate. Non-Newtonian behaviour is expected since the mixture showed a shear thinning effect when exposed to high shear stress. WLM is injected into the water flow test to determine the drag reducing efficiency in turbulent flow. Result from the water flow test proved that the both surfactant and polymer DRA can reduce the drag forces and hence improving flow rate. WLM is capable of performing the role of reducing the drag forces longer and more effective than polymeric DRA or PAM. The WLM system used in this research can improve the flow efficiency till 33.79% while PAM can improve the flow rate till a maximum of 20.38%.